Testicular melanization in anuran species: Ontogeny and sexual maturity - Goldberg, Javier; Valverde, Bruno S.L. [UNESP]; Franco-Belussi, Lilian (Brill Academic Publishers, 2020)
Testicular melanization in anurans may be absent or present with different degrees of intensity. When present, the color is due to the concentration of melanocytes in external (surface) and interstitial tissue. The function of this coloration is not fully known and we ask if melanization during testicular development, in species with highly pigmented testes in adults, is correlated with germ cells maturation. To do so, we selected four anuran species with highly pigmented testes. Species differed in the amount of interstitial melanin. Pigmentation increased throughout ontogeny, but with interspecific variation in the onset and rate. The rate of melanization progressed with testicular differentiation. A threshold for interstitial pigmentation seems to be reached with the advancement of spermatogenesis. Overall, testicular pigmentation adds a new chapter to the study of sexual maturity in anurans.
Keywords: anura; germ cells; interstitial tissue; pigmentation; sexual maturity; testicular development